CRM, learning and organizational control (Journal of Information Systems and Technology Management, 2006)
In this article are explored in a theoretical way the determinants of performance of Customer Relationship Management information systems that are established gradually in most of large companies. The approach adopted in this study focuses attention upon two central assumptions: the effect of the systems of CRM is mediated first by an increasing capability of organizational learning, and secondly through better organisational control devices.